Contrasting seasonal drivers of virus abundance and production in the North Pacific Ocean. - P Jackson Gainer; Helena L Pound; Alyse A Larkin; Gary R LeCleir; Jennifer M DeBruyn; Erik R Zinser; Zackary I Johnson; Steven W Wilhelm (PLoS ONE)
The North Pacific Ocean (between approximately 0°N and 50°N) contains the largest continuous ecosystem on Earth. This region plays a vital role in the cycling of globally important nutrients as well as carbon. Although the microbial communities in this region have been assessed, the dynamics of viruses (abundances and production rates) remains understudied. To address this gap, scientific cruises during the winter and summer seasons (2013) covered the North Pacific basin to determine factors that may drive virus abundances and production rates. Along with information on virus particle abundance and production, we collected a spectrum of oceanographic metrics as well as information on microbial diversity. The data suggest that both biotic and abiotic factors affect the distribution of virus particles. Factors influencing virus dynamics did not vary greatly between seasons, although the abundance of viruses was almost an order of magnitude greater in the summer. When considered in the context of microbial community structure, our observations suggest that members of the bacterial phyla Proteobacteria, Planctomycetes, and Bacteroidetes were correlated to both virus abundances and virus production rates: these phyla have been shown to be enriched in particle associated communities. The findings suggest that environmental factors influence virus community functions (e.g., virion particle degradation) and that particle-associated communities may be important drivers of virus activity.